Through Vuca Era: Learning from Women's Leadership in Open and Distance Higher Education during the Pandemic - Saleha, Eha; Tirtariandi El Anshori, Yuli; Sunarya, Amud; Amelia Nasution, Vivi Indra (Iapa Proceedings Conference, 2024)
Purpose: There is little research on women's leadership in Open and Distance Higher Education especially during the COVID-19 pandemic and times of uncertainty (VUCA) that explores women's experiences of leading a distance learning institution from home. This study describes how women managers of learning and materials services and heads of administration lead Universitas Terbuka from home in the implementation of the first phase of lockdown in Indonesia in 2020. Data collected in a narrative manner with in-depth interviews with four women about conscious experiences women lead the Jakarta and Serang regional offices of Universitas Terbuka. Leading from home requires extra energy for women at the beginning of the covid-19 pandemic, family support, technology and internet networks greatly affect the process of women's leadership in Universitas Terbuka. Work from home starting from office hours until late at night with commitment, proactive, trust and able to make decisions quickly with leadership and other staff through Microsoft Teams and Zoom. In addition, women leaders continue to communicate and coordinate via Whats-app group, personal communication and work email. Conclusions: The experience of working from home for women who lead open and distance higher education can be a positive picture behind the worrisome condition of the Covid-19 pandemic in the world.